Corporate actor networks in European policy making: Harmonizing telecommunications policy - Godefroy Dang Nguyen; Volker Schneider; Raymund Werle (Max-Planck-Institut für Gesellschaftsforschung, 1993)
The European Community as a social configuration, with its complex division of competencies and action capacities between EC institutions and national governments, is still difficult to conceptualize. In this context the authors propose the concept of corporate actor networks in order to understand more thoroughly the interaction processes of policy integration by which the European community has accumulated increasing supranational action capacities. A case study on the emergence and development EC telecommunications policy provides the background for a discussion of the scope, structure and operation of such EC policy actor networks. – – Mit ihrer komplexen Verteilung von Kompetenzen und Handlungskapazitäten zwischen den EG-Institutionen und den Mitgliedsstaaten ist das Sozialgebilde Europäische Gemeinschaft immer noch schwierig zu konzeptualisieren. Hierzu schlagen die Autoren das Konzept des Netzwerks korporativer Akteure vor. Dieses soll die Interaktionsprozesse zwischen den relevanten Akteuren in den Europäischen Gemeinschaften, welche der Integration verschiedener Politiken (policies) dienen, genauer fassen. Mittels einer Fallstudie über die Herausbildung und Entwicklung der EG-Telekommunikationspolitik wird ein Einblick in die Reichweite, Struktur und Operationsweise dieser transnationalen Politiknetzwerke auf EG-Ebene gegeben.
Keywords: 300